Brucella-Induced Downregulation of lncRNA Gm28309 Triggers Macrophages Inflammatory Response Through the miR-3068-5p/NF-κB Pathway - Deng, Xingmei; Guo, Jia; Sun, Zhihua; Liu, Laizhen; Zhao, Tianyi; Li, Jia; Tang, Guochao; Zhang, Hai; Wang, Wenjing; Cao, Shuzhu; Zhu, Dexin; Tao, Tingting; et al. (Frontiers in Immunology, 2020)
Objectives The underlying mechanism of the inflammatory response against Brucellosis caused by Brucella remains poorly understood. This study aimed to determine the role of long non-coding RNAs (lncRNAs) in regulating of inflammatory and anti-Brucella responses. Materials and methods Microarray analysis was performed to detect differentially expressed lncRNAs in THP-1 cells infected with an S2308 Brucella strain. The candidate lncRNAs were screened using bioinformatic analysis and siRNAs; bioinformatic prediction and luciferase reporter assay were also conducted, while inflammatory responses was assessed using RT‐qPCR, western blot, immunofluorescence, ELISA, HE, and immunohistochemistry. Results The lncRNA Gm28309 was identified to be involved in regulating inflammation induced by Brucella. Gm28309, localized in the cytoplasm, was down-expressed in RAW264.7 cells infected with S2308. Overexpression of Gm28309 or inhibition of miR-3068-5p repressed p65 phosphorylation and reduced NLRP3 inflammasome and IL-1β and IL-18 secretion. Mechanistically, Gm28309 acted as a ceRNA of miR-3068-5p to activate NF-κB pathway by targeting κB-Ras2, an inhibitor of NF-κB signaling. Moreover, the number of intracellular Brucella was higher when Gm28309 was overexpressed or when miR-3068-5p or p65 was inhibited. However, these effects were reversed by the miR-3068-5p mimic. Conclusions Our study demonstrates, for the first time, that LncRNAs are involved in regulating immune responses during Brucella infection, and Gm28309, an lncRNA, plays a crucial role in activating NF-κB/NLRP3 inflammasome signaling pathway.